2016
DOI: 10.1007/s00424-016-1876-8
|View full text |Cite
|
Sign up to set email alerts
|

Chronic atrial ionic remodeling by aldosterone: potentiation of L-type Ca2+ channels and its arrhythmogenic significance

Abstract: It is widely accepted that aldosterone induces atrial fibrillation (AF) by promoting structural changes, but its effects on the function of primary atrial myocytes remain unknown. We have investigated this point in adult rat atrial myocytes, chronically exposed to the hormone. This treatment produced larger amplitude of Ca transients, longer action potential (AP) duration, and higher incidence of unsynchronized Ca oscillations. Moreover, it also gave rise to increases in both cell membrane capacitance (C, 30 %… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Indeed, a previous study showed that MDIMP preferentially acts on LVA calcium currents of atrial myocytes, suggesting that Ca V 3 channels exhibit the highest affinity for this compound (Santamaria-Herrera et al, 2016). In these cells, the LVA calcium current is thought to reflect the activity not only of Ca V 3 channels (i.e., Ca V 3.1 and Ca V 3.2) but also Ca V 1.3 and Ca V 2.3 (Piedras-Rentería et al, 1997;Larsen et al, 2002;Zhang et al, 2005;Ríos-Pérez et al, 2016). Thus, the present study represents the first unequivocal demonstration that MDIMP preferentially binds to Ca V 3 channels.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Indeed, a previous study showed that MDIMP preferentially acts on LVA calcium currents of atrial myocytes, suggesting that Ca V 3 channels exhibit the highest affinity for this compound (Santamaria-Herrera et al, 2016). In these cells, the LVA calcium current is thought to reflect the activity not only of Ca V 3 channels (i.e., Ca V 3.1 and Ca V 3.2) but also Ca V 1.3 and Ca V 2.3 (Piedras-Rentería et al, 1997;Larsen et al, 2002;Zhang et al, 2005;Ríos-Pérez et al, 2016). Thus, the present study represents the first unequivocal demonstration that MDIMP preferentially binds to Ca V 3 channels.…”
Section: Discussionmentioning
confidence: 96%
“…Independently of its potential to be used clinically, MDIMP may also be helpful to dissect the activity of non-T-type calcium channels in native expression systems, specifically in conditions in which HVA channels exhibit characteristics typically associated with LVA channels, for example, in rat atrial myocytes in which the LVA calcium current is thought to reflect the activity of not only Ca V 3.1 and Ca V 3.2 but also Ca V 1.3 and Ca V 2.3 (Piedras-Rentería et al, 1997;Larsen et al, 2002;Zhang et al, 2005;Ríos-Pérez et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Production of ROS and NO was estimated using fluorescence sensors for these molecules (CM-H 2 DCF DA and DAF-FM DA; Ríos-Pérez et al, 2016). Either atrial or ventricular myocytes were incubated (15 min at room temperature) with Tyrode’s solution supplemented with a 1:1 mixture of Fura-2 AM and the appropriated sensor (3 μM each).…”
Section: Methodsmentioning
confidence: 99%